Genetic effect of basal metabolic rate on the benign neoplasm of bone and articular cartilage: a Mendelian randomization study - Huang, Guijin; Yao, Ying; Fan, Lin; Li, Sisi (Frontiers in Oncology, 2024)
BackgroundPrevious studies have found an association between basal metabolic rate (BMR) and various malignant neoplasms, including bone tumors. BMR is also associated with bone mineral density, but the causality between BMR and benign neoplasms of bone and articular cartilage remains uncertain.DesignSingle nucleotide polymorphisms (SNPs) associated with BMR (p < 5 × 10-8) were used as instrumental variables for Mendelian randomization analysis of neoplasm risk. The inverse variance weighted (IVW) method was the primary approach, with the weighted median and MR-Egger regression serving as supplements.ResultsIn this MR analysis, the IVW method supported a causal relationship between BMR and benign neoplasms of bone and articular cartilage (OR = 1.417; 95% CI, 1.039 to 1.930; p = 0.027). No evidence of heterogeneity or pleiotropy in the selected SNPs was found in our study. Thus, based on these results, we discovered a possible causal relationship between BMR and benign neoplasms of bone and articular cartilage.ConclusionsIn this MR study, evidence suggested a genetic correlation between genetically predicted BMR and the risk of neoplasms in bone and articular cartilage.